Analysis of The Driving Forces of Urban Expansion in Luxor City by Remote Sensing Monitoring - Mahmoud, Hatem; Alfons, Remon; M. Reffat, Rabee (International Journal of Integrated Engineering, 2019)
Luxor in Egypt is a city of great historical importance, rich in archaeological sites and natural resources. To ensure sustainable development in Luxor city, it is essential to understand the driving forces of its growth. Both Geographic Information Systems (GIS) and satellite Remote Sensing (RS) were successfully used to evaluate these overall driving forces. This paper is aimed at monitoring the growth dynamics of the urbanization process that occurred in Luxor city during a 20-year period from 1996 to 2017. The archived time series medium resolution Landsat ETM+ and TM satellite imagery are used to study and analyze spatial patterns of urban in order to improve understanding the impact of driving forces of urban expansion in Luxor. The GIS was not only used to identify the driving forces but also to provide an integrated monitoring of the study area. This offered a unique advantage to simultaneously store and manipulate spatial and attribute data of a large amount. A very significant increase in urban area has taken place in the last decade in Luxor city, which was revealed an important outcome. A net increase of 36.7 km2 was witnessed in the last 20 years (especially in recent years), in the built-up urban area. The built-up urban area in 2017 saw an increase that was twice that in 1996, with an annual average increase of 1.75 km2, and an annual change rate of 4.6%. The analysis of this dramatic change revealed that city infrastructure, economic growth, population growth, topographic elements, and city planning, and policies were the major driving forces for the rapid expansion of built-up urban area, albeit with different weights for these different forces. In this study, we explored a method of monitoring parameters related to the architectural heritage of Luxor governorate using â€œremote sensing big dataâ€ to provide data support for the cityâ€™s urban planning and policy formulation.